(3oZQQ GdHdGZIs - (3gdGd GdUCHjA , gdGd Hf GdeMSf Hf EHQGgje Hf gdGd GdMQGfj, CHh GdMSjf , CHh GdMSf,J (B448 (3g` s
(3ChdgG (B:s
(3hUd cJGH SjOfG eTJedkG ef GdaVd CYdeg, QjGVg GdeaYeI MjGVg, GdbGgQI CfhGQg, GdRGgQI CHcGQg s
(3BNQgG (B:s
(3hCNQS dSGf GdbGOM, hCOGe MeO GdMGeO, hhGUd ZjX GdMGSO HLhOg heLOg Je GdcJGH CLeY s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdLRA GdKGfj ef fSNI CNQis
(3hHgG JeGe GdcJGHs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs